Antiquorum sensing and biofilm potential of 5- Hydroxymethylfurfural against Gram positive pathogens. (December 2018) - Vijayakumar, Karuppiah; Ramanathan, Thiruganasambandam
Abstract: The present investigates the antiquorum sensing and biofilm inhibitory potential of 5 – hydroxymethylfurfural against Chromobacterium violaceum, Streptococcus pyogenes, Streptococcus mutans, Staphylococcus aureus and Staphylococcus epidermidis . 5HMF inhibits the quorum sensing mediated violacein pigment production by 87% at 100 μg/ml concentration. A 100 μg/ml concentration of the compound inhibits S. mutans and S. epidermidis biofilm formation by 86% and 79% whereas for S. pyogenes and S. aureus 125 μg/ml concentration inhibits biofilm formation by 83% and 82%. The Confocal images clearly indicate that 5HMF as a promising antibiofilm agent. Highlights: The present investigation proved 5 – Hydroxymethylfurfural (phytochemical) has the ability to inhibit quorum sensing, mediated biofilm formation in Gram positive pathogen . 5HMF reduced the quorum sensing mediated violacein pigment production in Chromobacterium violaceum.